LINGUISTIC CREATIVITY AND ACRONYMIC DERIVATION IN THE PENINSULAR SPANISH - IMMACULADA Fàbregas Alegret (Ибероамериканские тетради)
The investigation that we present is based on the ability to generate an endless number of words from a morphophonological process, in particular, acronymic derivation. We center our work on a delimited terri-tory: the peninsular Spanish. Throughout our study, we’ll show the latest creative tendencies in the subject of acronymic derivation in the Iberian Peninsula, using certain premises and targets that we’ll specify further. After a series of terminological clarifications, we’ll take as an observation area a lexical corpus that we’ll present and which analysis will allow us to draw some conclusions